Simulated surface tensions of common water models - Chen, Feng; Smith, Paul E. (My University, 2007)
Initial simulated values of the surface tension for the SPC/E water model have indicated excellent agreement with experiment. More recently, differing values have been obtained which are significantly lower than previous estimates. Here, we attempt to explain the differences between the previous studies and show that a variety of simulation conditions can affect the final surface tension values. Consistent values for the surface tensions of six common fixed charge water models (TIP3P, SPC, SPC/E, TIP4P, TIP5P, and TIP6P) are then determined for four temperatures between 275 and 350 K. The SPC/E and TIP6P models provide the best agreement with experiment.
Keywords: Water; Surface tension; Liquid theory; Interface phenomena